Literatur Review Elastisitas Penawaran Tenaga : Studi Empiris Pengujian Hipotesis Neoklasik dan Reference Dependent Preference - Wirya Wardaya (Journal of Economics Development Issues, 2022)
The extent to which wage levels affect labor supply is an important topic in labor economics. Empirical research is conducted to prove how the elasticity of labor supply in response to changes in the wage rate is whether the neoclassical hypothesis or the reference dependent-preference hypothesis applies. This study reviews the growth of empirical literature of the reference dependent preference hypothesis in the 2017-2022 period to enhance the critical review that presented in the literature review section based on early journals in 1997 - 2011. The results of this review found that that it rejects the neoclassical labor supply elasticity hypothesis and states that it is the reference dependent preference hypothesis